THU0351 The Role of Endoplasmic Reticulum Aminopeptidase 1 (ERAP1) in the Pathogenesis of Ankylosing Spondylitis. (23rd January 2014) - Cinar, M.; Akar, H.; Yilmaz, S.; Simsek, I.; Karkucak, M.; Sagkan, R. I.; Erdem, H.; Avci, I. Y.; Acikel, C.; Musabak, U.; Tunca, Y.; Pay, S.
Abstract : Background: Although genetic factors known to play crucial role in the pathogenesis of ankylosing spondylitis (AS), little is known about the molecular mechanisms that are responsible. In that context, endoplasmic reticulum aminopeptidase 1 (ERAP1) gene has been suggested as the most important factor in genetic susceptibility, with the exception of HLA-B27. Objectives: To investigate the role of ERAP1 in the pathogenesis of AS and its relationship with clinical findings. Methods: We included 150 consecutive AS patients who were fulfilling the Modified New York classification criteria and 150 blood donors as healthy control. DNA isolation from the participants' blood samples was performed automatically by the BioRobot ® EZ1 station and we investigated the presence of ERAP1 gene single nucleotide polymorphisms (SNPs) (rs30187, rs27044, rs26653, rs27037, rs2287987, rs10050860, rs17482078, rs7711564, rs27980, rs27529) by using the method of competitive allele-specific PCR. We also determined the subgroups of HLA-B27 by PCR-Sequence Specific Primer (SSP). The differences between genotype and allele frequencies were compared by Pearson Chi-square test. Results: The mean age of patients and controls were 34.6 and 29.4 years, respectively. In the patient group, the rate of HLA-B27 positivity was 66.7%, while this was 4.7% in the control group. We detected rs26653 SNP C/C homozygotes in 36 patients (24.0%) and 21 controls (14.0%). The frequency distribution of rs26653 SNP C/C homozygous genotype between the groups was found to be statistically significant (p=0.015). We identified that the frequency of rs26653 SNP's risky C allele was higher in the patient group (50.0%) than the control group (38.3%) (OR 1.609, %95 CI 1.163-2.226, p=0.004). The contribution of rs26653 SNP's risky C allele to the total AS genetic risk was calculated as 23.4%. The differences between genotype and allele frequency distribution of other SNPs were not statistically significant. Conclusions: In our study, only rs26653 SNP, out of 10 ERAP1 gene SNPs, which were suggested as genetic susceptibility factors in AS at previous studies, was found to be associated with the risk of genetic predisposition in our AS group. The contribution of rs26653 SNP to the total AS genetic risk in the present study was found as 23.4% and it was compatible with the literature (26%). Since there was no relation between HLA-B27 positivity and rs26653 SNP, the contribution of both factor to the pathogenesis of AS seems to be independent from each other. Disclosure of Interest: None Declared